Advertisement Remove all ads

Solve for X : 4x-1 × (0.5)3 - 2x = (1/8)^-x - Mathematics

Sum

Solve for x :  4x-1 × (0.5)3 - 2x = `(1/8)^-x`

Advertisement Remove all ads

Solution

4x-1 × (0.5)3 - 2x = `(1/8)^-x`

⇒ `(2^2)^(x - 1) xx (1/2)^( 3 - 2x ) = ( 1/2^3 )^(-x)`

⇒ 22x - 2 x 2-( 3 - 2x ) = (2 -3)- x

⇒ 22x - 2 - 3 + 2x = 23x

⇒ 24x - 5 = 23x
⇒ 4x - 5 = 3x
⇒ 4x - 3x = 5
⇒ x = 5

Concept: Solving Exponential Equations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 9 ICSE
Chapter 7 Indices (Exponents)
Exercise 7 (B) | Q 14.1 | Page 101
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×